Awareness and knowledge of human papilloma virus (HPV) vaccine in prevention of cervical cancer among medical students - M., Radhika; Sadiqunissa, Sadiqunissa; Ahmed, Mehfooza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cervical cancer is the most common malignancy amongst women in India. Identification and prevention of the pre-cancerous lesions helps to reduce the incidence of Carcinoma of cervix. The main aim of the study is to know the awareness and knowledge of HPV vaccine in prevention of cervical cancer among medical students. Methods: The study included 97 medical students (final year) studying in Yenepoya Medical College, Mangalore. It is a cross-sectional questionnaire-based study. Results: The results of awareness and knowledge about the HPV vaccine are interpreted in percentage. In this study, 76% of study subjects were aware that cancer cervix is preventable, 80% of the study subjects were aware about the association between the causation of cancer cervix by HPV. Majority of the study subjects about 72% ware about the vaccines for HPV but, awareness about the cost and efficacy of the vaccine was low only about 30% and 10% respectively. However, importantly students had a positive attitude to educate people regarding HPV vaccination and also to clear myths and misconceptions. Conclusions: Medical students should be educated regarding HPV infection, risk factors for causation of cervical cancer, screening methods which are available, HPV vaccines available in India and also about the efficacy and to motivate the society to have a positive attitude towards HPV vaccination by clearing the misconceptions regarding its information.